Asymmetric Dimethylarginine in Adult Falciparum Malaria: Relationships With Disease Severity, Antimalarial Treatment, Hemolysis, and Inflammation. (9th February 2016) - Barber, Bridget E.; William, Timothy; Grigg, Matthew J.; Parameswaran, Uma; Piera, Kim A.; Yeo, Tsin W.; Anstey, Nicholas M.
Abstract : Asymmetric Dimethylarginine (ADMA) and arginine bioavailability are reduced acutely in adult falciparum malaria. ADMA increases following commencement of antimalarial therapy, is associated with arginine and haemolysis, and likely contributes to reduced nitric oxide bioavailability in severe falciparum malaria. Abstract: Background.  Endothelial nitric oxide (NO) bioavailability is impaired in severe falciparum malaria (SM). Asymmetric dimethylarginine (ADMA), an endogenous inhibitor of NO synthase (NOS), contributes to endothelial dysfunction and is associated with mortality in adults with falciparum malaria. However, factors associated with ADMA in malaria, including the NOS-substrate l -arginine, hemolysis, and antimalarial treatment, are not well understood. Methods.  In a prospective observational study of Malaysian adults with SM (N = 22) and non-SM (NSM; N = 124) and healthy controls (HCs), we investigated factors associated with plasma ADMA including the effects of antimalarial treatment. Results.  Compared with HCs, ADMA levels were lower in NSM (0.488 µM vs 0.540 µM, P = .001) and in the subset of SM patients enrolled before commencing treatment (0.453 µM [N = 5], P = .068), but levels were higher in SM patients enrolled after commencing antimalarial treatment (0.610 µM [N = 17], P = .026). In SM and NSM, ADMA levels increased significantly to above-baseline levels by day 3. Baseline ADMA was correlated with arginine and cell-free hemoglobin in SM and NSM and inversely correlated with interleukin-10 in NSM. Arginine and the arginine/ADMA ratio (reflective of arginine bioavailability) were lower in SM and NSM compared with HCs, and the arginine/ADMA ratio was lower in SM compared with NSM. Conclusions.  Pretreatment ADMA concentrations and l -arginine bioavailability are reduced in SM and NSM. Asymmetric dimethylarginine increases to above-baseline levels after commencement of antimalarial treatment. Arginine, hemolysis, and posttreatment inflammation all likely contribute to ADMA regulation, with ADMA likely contributing to the reduced NO bioavailability in SM.